Bob Marley's Radio Interviews in Britain and the USA, 1973-1980: Reasoning with Issues of Absence and Presence. Issue 2 (4th May 2019) - Hajimichael, Mike
ABSTRACT: Bob Marley conducted many interviews with different media outlets in a relatively short period as an international artist. I researched these interviews and examined their content with regard to categories based on interview format, style, and media representation (who speaks?). A sample of interviews is considered in detail, including interviews by Neville Willoughby, John Peel, John Tobler, and David Rodigan, plus key audio and radio resources from Marley archivist-collector Roger Steffens. Consideration is given to how these resources exist today online and to what extent they have been preserved, adapted, edited, and used.